The Role of Islamic Religious Education in Preventing the Entry of Foreign Cultures - Saepuloh Pikri; Wahyudi; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - This article was written to explain the relationship between religion and modern culture from an Islamic perspective and to explain the attitudes of religious people in responding to modern culture. Modern culture poses a big challenge for Muslims in the world, especially in Indonesia. This certainly affects the existence of religions in the world, especially Islam. Modern culture is suspected of making significant changes and threatening the existence of religion within religious communities. The religious needs of mankind are shrinking as the modern culture develops, even religion in modern culture may no longer be needed because all the needs of mankind can be met with advances in science and technology. On the other hand, the religion which is used as a guide in dealing with various situations seems less responsive to the progress of the times. For this reason, the relationship between religion and modern culture needs to be formatted, this article explains that the relationship between the two begins with vertical and horizontal relations, which are then translated into relations in the form of indigenization, negotiation, and conflict. From this relationship, the attitudes of religious people arise, namely refusing, fully accepting, and analyzing first before deciding.